Activity of the Tobacco Industry in Research and Scientific Literature - Markus Braun; Doris Klingelhöfer; Dörthe Brüggmann; David A. Groneberg (Tobacco Use Insights, 2024)
Introduction Tobacco companies conduct and fund research. They are not always interested in open-ended research. They promote their interests through public relations campaigns. It’s a proven fact that they influence the scientific community by impairing scientific reputation, especially in the case of health-related research. Methods To obtain a comprehensive picture of research and funding activities of the tobacco industry as well as studies about the tobacco industry, respective scientific articles were analyzed in terms of temporal aspects, research areas, networking, and funding sources using established and advanced bibliometric methods. Results We found the foci of publications with tobacco industry involvement or funding were mainly in chemistry, toxicology, pharmacology, and agricultural sciences. Health-related scopes occurred much less frequently. In contrast, health and medical sciences were the main focus of publications on the tobacco industry. The Chinese state-owned CNTC was the most research-involved tobacco company and often networked with Chinese academic institutions. Whereas, Western universities, on the other hand, collaborated with tobacco companies to a much lesser extent. Conclusion Conflicts of interest of researchers or academic institutions with the tobacco industry occur repeatedly. That is highly problematic and should not be ignored by the scientific community. The science and the public should be skeptical about tobacco industry-supported research.